Turbulence and Interactions Proceedings of the TI 2015 Conference, June 11-14, 2015, Cargèse, Corsica, France - Deville, Michel O.; Couaillier, Vincent; Estivalezes, Jean-Luc.; Gleize, Vincent; HiêpLê, Thiên; Terracol, Marc.; Vincent, Stéphane; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents a snapshot of the state-of-art in the field of turbulence modeling, with an emphasis on numerical methods. Topics include direct numerical simulations, large eddy simulations, compressible turbulence, coherent structures, two-phase flow simulation and many more. It includes both theoretical contributions and experimental works, as well as chapters derived from keynote lectures, presented at the fourth Turbulence and Interactions Conference (TI 2015), which was held on June 11-14 in Cargèse, Corsica, France. This multifaceted collection, which reflects the conference´s emphasis on the interplay of theory, experiments and computing in the process of understanding and predicting the physics of complex flows and solving related engineering problems, offers a timely guide for students, researchers and professionals in the field of applied computational fluid dynamics, turbulence modeling and related areas.
Keywords: Fluid mechanics; Continuum mechanics; Dynamics; Nonlinear theories; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Fluid Dynamics; Continuum Mechanics; Applied Dynamical Systems; Engineering Thermodynamics, Heat and Mass Transfer